О корректной разрешимости нелокальной краевой задачи для систем гиперболических уравнений с импульсными воздействиями - Асанова, А.Т. (Український математичний журнал, 2015)
Встановлено взаємозв'язок між коректною розв'язністю нелокальної крайової задачi з імпульсним впливом для системи гіперболічних рівнянь і коректною розв'язністю сім'ї двоточкових крайових задач з імпульсним впливом для системи звичайних диференціальних рівнянь. На основі методу введення функціональних параметрів отримано достатні умови існування єдиного розв'язку сім'ї двоточкових крайових задач з імпульсним впливом для системи звичайних диференціальних рівнянь i запропоновано алгоритми знаходження її розв'язків. Одержано необхідні та достатні умови коректної розв'язності нелокальної крайової задачі для системи гіперболічних рівнянь другого порядку с імпульсним впливом в термінах вихідних даних. We consider a nonlocal boundary-value problem for a system of hyperbolic equations with impulsive effects. The relationship is established between the well-posed solvability of the nonlocal boundary-value problem for a system of hyperbolic equations with impulsive effects and the well-posed solvability of a family of two-point boundary-value problems for a system of ordinary differential equations with impulsive effects. Sufficient conditions for the existence of a unique solution of the family of two-point boundary-value problems for a system of ordinary differential equations with impulsive effects are obtained by method of introduction of functional parameters. The algorithms are proposed for finding the solutions. The necessary and sufficient conditions of the well-posed solvability of a nonlocal boundary-value problem for a system of hyperbolic equations with impulsive effects are established in the terms of the initial data.